A human liver cell-based system modeling a clinical prognostic liver signature for therapeutic discovery - Emilie Crouchet (Nature Portfolio, 2021)
Drug and target discovery for advanced liver disease are hampered by a lack of suitable models for clinical translation. Here the authors present a human liver cell-based system modeling a clinical prognostic signature allowing to propose nizatidine for treatment of advanced liver fibrosis and hepatocellular carcinoma prevention.